2020
DOI: 10.1128/mbio.00737-20
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3C Tandem Domain Proteins Create Super Restriction Factors against HIV-1

Abstract: Humans encode proteins, called restriction factors, that inhibit replication of viruses such as HIV-1. The members of one family of antiviral proteins, apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like 3 (APOBEC3; shortened here to A3), act by deaminating cytidines to uridines during the reverse transcription reaction of HIV-1. The A3 locus encodes seven genes, named A3A to A3H. These genes have either one or two cytidine deaminase domains, and several of these A3s potently restrict HIV-1. A3C, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 50 publications
3
17
0
Order By: Relevance
“…This higher anti-HIV activity of S188I was attributed to the gained ability to form dimer, which is supported by the evidence from size exclusion chromatography (SEC) and cross-linking experiments [ 116 , 132 ]. This notion is further strengthened by the similarly enhanced anti-HIV activity of a forced tandem dimer through linking two A3C or two S188I variants together [ 116 , 132 , 134 ]. These results indicate that forced dimerization is sufficient to significantly increase the anti-HIV activity regardless of the A3C S188 or the I188 variant at position 188 [ 116 , 132 , 134 ].…”
Section: Apobec3c (A3c)mentioning
confidence: 99%
See 1 more Smart Citation
“…This higher anti-HIV activity of S188I was attributed to the gained ability to form dimer, which is supported by the evidence from size exclusion chromatography (SEC) and cross-linking experiments [ 116 , 132 ]. This notion is further strengthened by the similarly enhanced anti-HIV activity of a forced tandem dimer through linking two A3C or two S188I variants together [ 116 , 132 , 134 ]. These results indicate that forced dimerization is sufficient to significantly increase the anti-HIV activity regardless of the A3C S188 or the I188 variant at position 188 [ 116 , 132 , 134 ].…”
Section: Apobec3c (A3c)mentioning
confidence: 99%
“…This notion is further strengthened by the similarly enhanced anti-HIV activity of a forced tandem dimer through linking two A3C or two S188I variants together [ 116 , 132 , 134 ]. These results indicate that forced dimerization is sufficient to significantly increase the anti-HIV activity regardless of the A3C S188 or the I188 variant at position 188 [ 116 , 132 , 134 ]. This significantly enhanced anti-HIV activity cannot be accounted for by the slight increase of deaminase activity and the virion package level, which highlights the importance of dimerization of A3C in restricting HIV.…”
Section: Apobec3c (A3c)mentioning
confidence: 99%
“…Another interesting challenge is the creation of a “super restriction factor” to function as an inhibitor more potent than the original protein ( McDonnell et al, 2020 ). Single-domain deaminase A3C proteins have weak HIV-1 restriction activity compared with that of double-domain deaminases, e.g., A3D, A3F, and A3G proteins ( Bishop et al, 2004 ; Hultquist et al, 2011 ; Wittkopp et al, 2016 ; Anderson et al, 2018 ).…”
Section: Potential Utilization Of Vif-resistant A3 Proteins For An Hiv-1 Functional Curementioning
confidence: 99%
“…Single-domain deaminase A3C proteins have weak HIV-1 restriction activity compared with that of double-domain deaminases, e.g., A3D, A3F, and A3G proteins ( Bishop et al, 2004 ; Hultquist et al, 2011 ; Wittkopp et al, 2016 ; Anderson et al, 2018 ). Synthetic tandem double deaminase A3C proteins represent one attempt to create HIV-1 restrictive A3C proteins that are more potent than the native proteins ( McDonnell et al, 2020 ). The novel double-domain A3C proteins showed improved HIV-1 restriction activity and were largely resistant to Vif-mediated degradation.…”
Section: Potential Utilization Of Vif-resistant A3 Proteins For An Hiv-1 Functional Curementioning
confidence: 99%
“…For example, not all of the double Z domain combinations have been sampled in primates, and many combinations of A3 double domains with polymorphisms are unsampled [12]. We predicted that novel double domain combinations may prove to be more effective inhibitors of HIV-1 and we refer to these kinds of evolutionary-based variants of natural antiviral proteins with improved potency and/or escape from antagonism as "super restriction factors" [21][22][23]. Our previous study showed that duplicating the single A3Z2 domain protein A3C created an A3C-A3C tandem domain protein with increased antiviral activity relative to its single domain counterpart that was also largely resistant to degradation by HIV-1 Vif [22].…”
Section: Introductionmentioning
confidence: 99%